A Life-Transformative Education for the 21st Century: Exploring, Creating, and Leading Through Honors - Chancey, Jaclyn M.; Lease Butts, Jennifer (International Journal for Talent Development and Creativity, 2020)
This article explores the theoretical underpinnings of life-transformative education and gifted education and applies them to a university honors program. Life-transformative education requires authentic learning experiences and rich mentorship relationships to promote happiness, well-being, and a sense of purpose. This is intended for all students, so the literature on gifted education is used to differentiate an honors education. Several competing paradigms exist, and the University of Connecticut Honors Program bases its theoretical framework and program design on the talent development models of Joseph Renzulli. The article concludes with a closer look at the honors leadership experience and preparing students to solve 21st century problems.